Assessment of Platelet and Plasma Serotonin in Canine Pulmonary Hypertension Secondary to Degenerative Mitral Valve Disease - Tangmahakul, Nattawan; Makoom, Pussadee; Surachetpong, Sirilak Disatian (Frontiers in Veterinary Science, 2021)
Background: Pulmonary hypertension (PH) is a common complication of degenerative mitral valve disease (DMVD), the most common cardiovascular disease in dogs. Serotonin has been suspected to play a role in the pathogenesis of PH, so this study aimed to investigate the differences in platelet and plasma serotonin between normal, DMVD and DMVD with PH (DMVD+PH) dogs. Materials and Methods: Sixty-two small-breed dogs were enrolled to the study and divided into the normal (n = 22), DMVD (n = 20), and DMVD+PH (n = 20) groups. The platelet and plasma serotonin concentrations were measured by the competitive ELISA. Results: The Mann-Whitney U test showed a decrease in platelet serotonin concentrations in the DMVD+PH group (135.11 [21.21–312.22] ng/109 platelets) compared to the DMVD group (325.99 [ 96.84–407.66] ng/109 platelets) (p = 0.03). The platelet serotonin concentration was decreased in dogs with a high probability of PH (35.82 [2.69—126.35] ng/109 platelets) compared to those with an intermediate probability of PH (291.11 [106.69-400.84] ng/109 platelets) (p=0.02). The plasma serotonin concentration was not different between normal, DMVD and DMVD+PH dogs. Conclusion: In conclusion, a decrease in platelet serotonin concentration, which is associated with a degree of PH probability was found in DMVD dogs with PH. Further studies investigating roles of platelet serotonin in PH secondary to DMVD should be performed.